1980
DOI: 10.1136/bmj.280.6209.207
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy in childhood: findings from the National Child Development Study.

Abstract: Summary and conclusionsBy the age of 11 years 1043 children (6-7%) in an unselected national sample had a history of seizures or other episodes of loss of consciousness; 322 (20 8/1000) had a history offebrile convulsions without other epileptic problems. A clear-cut diagnosis of non-febrile epilepsy was established in 64 children (41/1000) by the age of 11 on the basis of confirmatory information supplied by family doctors and paediatricians. A further 39 (2-6/1000) were reported as having epilepsy but did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
92
2
1

Year Published

1984
1984
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(110 citation statements)
references
References 13 publications
15
92
2
1
Order By: Relevance
“…Recent epidemiologic studies have confirmed what most pediatricians have thought for decades, that the vast majority of children with febrile seizures have a benign prognosis and a normal long-term outcome (1)(2)(3)(4)(5)(6)(7). There are, however, still unsolved problems.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…Recent epidemiologic studies have confirmed what most pediatricians have thought for decades, that the vast majority of children with febrile seizures have a benign prognosis and a normal long-term outcome (1)(2)(3)(4)(5)(6)(7). There are, however, still unsolved problems.…”
mentioning
confidence: 78%
“…Adverse outcome may be more related to an underlying preexisting cerebral condition than to the seizure itself (13,14). Even though febrile status appears to have a much better prognosis than hitherto believed (2,4,(14)(15)(16) it should still be considered a major pediatric emergency, requiring fast and aggressive treatment.…”
Section: Short-term Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…12,13 The present study quantifies the amount that retrospectively collected data underestimates the incidence rate of prospectively collected data (considered to be the accurate rate of FS). 14 However, the difference was significant only for females, which is an observation that is difficult to explain.…”
Section: Discussionmentioning
confidence: 99%
“…Prior epidemiologic studies of the outcome of febrile seizures in both United States 14 and the United Kingdom 15,16 also have not found differences in global cognitive outcomes between children with febrile seizures and either siblings 14 or population controls, 15,16 but these studies did not specifically examine memory. Interestingly, seizure onset before 1 year of age was also a risk factor for poor outcome in the recent British study.…”
mentioning
confidence: 99%